Treatment of Facial Asymmetry and Temporomandibular Joint Ankylosis by Distraction Osteogenesis: A Case Report - Dabla, Neetu; Prasad, P Narayana; Vedvyas, Arjun; Aggarwal, Richa (Orthodontic Journal of Nepal, 2013)
Facial asymmetry and functional problems due to dentofacial discrepancy and soft tissue disparities are commonly managed by orthognathic surgery and augmentation procedures. Distraction osteogenesis is a relatively new technique of bone generation and reconstruction. A patient reported with the chief complaint of asymmetry of face and deviated chin; had temporomandibular joint ankylosis. Distraction device was applied with simultaneous release of ankylosis by gap arthroplasty. For management of mandibular deformity and discrepancy of the dentition, orthodontic therapy was done using MBT 0.022” prescription. Distraction was stopped when the midline of upper central incisor coincided with the midline of lower central incisor followed by stabilization period of ten weeks. The functional and esthetic results achieved were acceptable.